Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/adma.201806484
|View full text |Cite
|
Sign up to set email alerts
|

Comb and Bottlebrush Polymers with Superior Rheological and Mechanical Properties

Abstract: combined with the grafting-to method [1,10] results in comb polystyrenes (PSs) with well-entangled monodisperse backbone and side chains; however, branch points along the backbone are randomly distributed. This random distribution of branch points has no distinct effect on the rheological properties of dense comb topologies; however, it will broaden the backbone relaxation time of loose comb topologies even though the molecular weight distribution is narrow enough. [11] A controlled branching point spacing can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(152 citation statements)
references
References 70 publications
(187 reference statements)
3
145
1
1
Order By: Relevance
“…Interestingly, η 0 exhibited different behavior in each conformational regime. LC PS behaved like star molecules where η 0 increased exponentially as a function of M w (η 0~e xp (M w )), which is related to the strong frictional effect of the branches on the backbone [22]. A further increase of N br resulted in a continuous decrease of η 0 , reflecting the dilution effect of the branches.…”
Section: Saos Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, η 0 exhibited different behavior in each conformational regime. LC PS behaved like star molecules where η 0 increased exponentially as a function of M w (η 0~e xp (M w )), which is related to the strong frictional effect of the branches on the backbone [22]. A further increase of N br resulted in a continuous decrease of η 0 , reflecting the dilution effect of the branches.…”
Section: Saos Resultsmentioning
confidence: 98%
“…They also investigated the effect of the number of branches on the linear viscoelastic (zero-shear viscosity) and nonlinear viscoelastic properties (extensional viscosity and strain hardening factor) of the model comb PS set. The results showed that a relative minimum in the zero-shear viscosity and a maximum in strain hardening factor were observed near a transition point from DC to LB, which was associated with the stretched backbone conformation grafted with crowding side chains [21,22]. Up to now, most rheological studies on bottlebrush polymers have focused on linear shear flow [20,23,24] and extensional flow [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…If the ink has a relatively high initial viscosity, then the ability of the ink to retain its shape after exiting the nozzle can allow for continuous printing without the need for a curing step between layers. Desired ink rheologies can be achieved through clever molecular design of polymer side chains . Most of the inks currently being developed for DIW systems utilize shear‐thinning dispersions or pastes to achieve high shape retention upon immediate exiting of the nozzle.…”
Section: Additive Manufacturing Of Conjugated Polymersmentioning
confidence: 99%
“…(c,d) Bowl structure with 58° overhang angle successfully printed with conductive PANI‐based ink. (Reproduced from , with permission from IOP Publishing.) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Additive Manufacturing Of Conjugated Polymersmentioning
confidence: 99%
See 1 more Smart Citation